Mitochondrial Metabolism as a Target for Cancer Therapy - Vasan, Karthik; Werner, Marie; Chandel, Navdeep S. (Cell metabolism, 2020)
Recent evidence in humans and mice supports the notion that mitochondrial metabolism is active and necessary for tumor growth. Mitochondrial metabolism supports tumor anabolism by providing key metabolites for macromolecule synthesis and generating oncometabolites to maintain the cancer phenotype. Moreover, there are multiple clinical trials testing the efficacy of inhibiting mitochondrial metabolism as a new cancer therapeutic treatment. In this review, we discuss the rationale of using these anti-cancer agents in clinical trials and highlight how to effectively utilize them in different tumor contexts. Recent evidence indicates that mitochondrial metabolism is essential for tumorigenesis. Vasan et al. review multiple mitochondrial drugs in clinical trials for various cancers, including metformin. Also, they report a genetic screen highlighting mechanisms of resistance to metformin.